2012
DOI: 10.1155/2012/354904
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Effect of Infant Rats Endotoxemia on Heat Shock Protein 60 in the Pancreatic Acinar Cells: Involvement of Toll-Like Receptor 4

Abstract: Introduction. Lipopolysaccharide endotoxin (LPS) is responsible for septic shock and multiorgan failure, but pretreatment of rats with low doses of LPS reduced pancreatic acute damage. Aim. We investigated the effects of the endotoxemia induced in the early period of life on Toll-like receptor 4 (TLR4), heat shock protein 60 (HSP60) and proapoptotic Bax, caspase-9 and -3 or antiapoptotic Bcl-2 protein expression in the pancreatic acinar cells of adult animals. Material and Methods. Newborn rats (25 g) were inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Pancreatic acinar cells were isolated by collagenase digestion as described previously [ 112 , 113 ] and incubated in cerulein-free or cerulein containing solution. Previous studies showed that cerulein given at a concentration of 10 −8 M and 5-h incubation were most effective in stimulating exocrine secretion and gene expression in pancreatic acinar cells [ 114 , 115 ], thus these concentration of cerulein and time of incubation were selected for our current in vitro studies. Studies in each experimental group were repeated at least six times.…”
Section: Methodsmentioning
confidence: 99%
“…Pancreatic acinar cells were isolated by collagenase digestion as described previously [ 112 , 113 ] and incubated in cerulein-free or cerulein containing solution. Previous studies showed that cerulein given at a concentration of 10 −8 M and 5-h incubation were most effective in stimulating exocrine secretion and gene expression in pancreatic acinar cells [ 114 , 115 ], thus these concentration of cerulein and time of incubation were selected for our current in vitro studies. Studies in each experimental group were repeated at least six times.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that TLR4 expression was increased in pancreatic acinar cell after acute pancreatitis induced by caerulein injections or by taurocholate infusion [55,56]. LPS treatment and caerulein over-stimulation increased TLR4 content in isolated rat pancreatic acini [57]. TLR9 activation was found to stimulate pancreatic stellate cell proliferation and tumorigenesis [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…saline or GHRL. After isolation, pancreatic acinar cells were incubated in caerulein-free or caerulein containing solution [ 126 , 127 ]. Caerulein concentration was 10 −8 M, incubation time was 5 h.…”
Section: Methodsmentioning
confidence: 99%